Avaliação de desempenho por competências: percepção de analistas das agências regionais do Sebrae/PB - Lima, Maria Antônia Gonçalves da Silva (2023)
Good organizational performance is related to the performance of each member of the organization. In this sense, the present dissertation proposed to investigate the relevance and contribution of performance assessment by competences for individual and organizational learning. The analysis was based on the case study of the Serviço de Apoio às Micro e Pequenas Empresas (Sebrae) in Paraíba, based on the perception of analysts at the regional agencies of this organization. Sebrae/PB consists of an entity that applies this type of assessment, whose dynamics, criteria and others are defined by its Personnel Management System (SGP). The study was based on the considerations of relevant scholars on the subject, as well as the meticulous detailing of the evaluation as provided for in the SGP, and interview with twelve employees of the entity, in order to understand their perception of the performance evaluation process by competencies and how it reverberates at the individual and organizational levels. Reflections and analyzes regarding the case were carried out in the light of the main theories and concepts related to the area, such as those related to competences and people management, learning in contemporary organizations and the management system based on competences in organizations. As a result, it was identified that the SGP evaluation process is necessary for employee recognition, as well as for their progression, as it is organized based on well-defined criteria. However, it lacks improvements to ensure the effectiveness of the system, such as reducing the time in the evaluation and feedback process, making it more open, dynamic and with more continuous and flexible deadlines. Finally, as a proposal, it was observed the need to consider actions such as reviewing the training process and the construction of a communication method in which there is, an effective way, the clarification of the main doubts of the employees about the evaluation of the organization's performance and updating the system version so that both assessment and feedback occur in a shorter period of time.